2016
DOI: 10.1155/2016/2912418
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of High Dietary Tryptophan on Intestinal Morphology and Tight Junction Protein of Weaned Pig

Abstract: Tryptophan (Trp) plays an essential role in pig behavior and growth performances. However, little is known about Trp's effects on tight junction barrier and intestinal health in weaned pigs. In the present study, twenty-four (24) weaned pigs were randomly assigned to one of the three treatments with 8 piglets/treatments. The piglets were fed different amounts of L-tryptophan (L-Trp) as follows: 0.0%, 0.15, and 0.75%, respectively, named zero Trp (ZTS), low Trp (LTS), and high Trp (HTS), respectively. No signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 24 publications
5
43
1
1
Order By: Relevance
“…The present results also showed that the main antioxidant enzyme, GCLc, decreased in percentage in the jejunum after diquat injection. These results indicate that diquat induced oxidative stress in piglets, which is in accordance with the previous research [7,20,25,26].…”
Section: Discussionsupporting
confidence: 93%
“…The present results also showed that the main antioxidant enzyme, GCLc, decreased in percentage in the jejunum after diquat injection. These results indicate that diquat induced oxidative stress in piglets, which is in accordance with the previous research [7,20,25,26].…”
Section: Discussionsupporting
confidence: 93%
“…An excessive increase in the activity of these viscera could depress the growth performance by decreasing the organic function and enzymatics of the birds. On the other hand, protein-rich feeds such as canola meal increase the relative weight of the liver in broiler by the high concentration of glucosinolate (Tossou et al, 2016;Woyengo, Kiarie, & Nyachoti, 2011). It is worth noting that the biological responses depend on dietary components.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, its production stimulated peripheral monocytes [40]. Tossou et al reported that tryptophan played the role of regulating physiological functions and intestinal permeability in the alimentary tract [41]. Hyeyoung Kim reviewed the glutamine, another essential immune nutrient.…”
Section: Discussionmentioning
confidence: 99%